Cultivating the past, living the modern the politics of time in the Sultanate of Oman - Sachedina, Amal, 1974- (Cornell University Press, 2021)
"Centered in Muscat and Nizwa, the book analyzes the relations with the past that undergird the shift in Oman from an Ibadi shari'a Imamate (1913-1958) to a modern nation state from 1970 onwards. Key locales and objects become sites for tracking transformations in forms of history, religious and political authority"--